Editorial: Instruments and support practices for the achievement of Open Science goals – For a review of data in Criminal Procedural Law - Bruna Capparelli (Revista Brasileira de Direito Processual Penal, 2018)
This article discusses the applicability of open peer review to criminal investigation data. First, it means identifying the strengths and weaknesses of the dataset review and validation process. Second, there will be evidence of practices that facilitate process transparency, data diffusion, reliability and reuse. To achieve these objectives, it will be argued that it is necessary to adopt a methodology on which to base the selection criteria of the scientific community of reference, to identify the types of actors and the relative modalities of analysis, at the moment when the construction of a collaborative and participative context is the first step to delimit a community representative of the criminal process and its different research techniques.